Current situation and future outlook of production, processing and marketing in the celery industry - Pei-Zhuo Liu; Ya-Hui Wang; Li-Xiang Wang; Meng-Yao Li; Hui Liu; Sheng Shu; Guo-Fei Tan; Ai-Sheng Xiong (Technology in Horticulture)
China is the largest vegetable-producing country in the world, with annual production accounting for more than 50% of the total world production. Celery is a major leafy vegetable and has rich nutritional and medicinal values. In recent years, celery production has been steadily developing in all parts of China under the environment of good operation of the overall vegetable industry market. Many concentrated and contiguous large-scale celery production areas are spread in both north and south of China. However, the current celery industry still needs improvement in the creation of an intensive production system, prevention of premature bolting, prevention and control of pests and diseases, development of deep processing products, marketing, brand protection, and other aspects. In the future, with the improvement of cultivation technology, the intensification of production is expected to be further improved. At the same time, it is necessary to solve the problems in celery production through the cooperation between scientific research institutions and production enterprises, to promote the rapid development of the celery industry.